Recycle Pekat (Perca Kain Tenunan) Flores Dalam Meningkatkan Kreativitas Mahasiswa Dan Kepedulian Lingkungan - Nunur, Maria Melita; Lue, Bernadina Oswin; Gobang, Paulina Masliani; Repe, Maria Restina; Sewo, Febriyanti Malan; Ningsih, Ningsih; Seto, Stefania B; Wondo, Maria Trisna Sero (Ekspektasi: Jurnal Pendidikan Ekonomi, 2023)
Woven fabric is a decorative variety in Indonesia that is widespread in every region of the archipelago from Sabang to Merauke, characterized by various motifs, patterns, colors and meanings. Woven cloth developed in East Nusa Tenggara is a craft art that has been taught to children and grandchildren from generation to generation. However, it is a shame because currently most of the younger generation cannot weave. This will have an impact on the extinction of ikat fabrics. Efforts made to ensure that woven fabric does not become extinct are by re-preserving its existence and re-introducing its use. One way to preserve it is by recycling woven fabric patchwork waste into products in the form of earrings, necklaces, bracelets, hairpins, brooches, bags and hats which have several benefits such as preserving local cultural products, namely typical Flores woven fabrics. In an effort to produce products, of course there are stages, namely the preparation stage of materials and tools, the production stage, packaging to marketing and then continuing with product marketing techniques.